Obesity is Independently Associated With Increased Risk of Hepatocellular Cancer–related Mortality: A Systematic Review and Meta-Analysis. (September 2018) - Gupta, Arjun; Das, Avash; Majumder, Kaustav; Arora, Nivedita; Mayo, Helen G.; Singh, Preet P.; Beg, Muhammad S.; Singh, Siddharth
Abstract : Objective: Excess body weight is associated with increased risk of developing hepatocellular cancer (HCC), but its effect on HCC-related mortality remains unclear. We performed a systematic review and meta-analysis to assess the association between premorbid obesity and HCC-related mortality. Materials and Methods: Through a systematic literature search-up to March 2016, we identified 9 observational studies (1, 599, 453 individuals, 5705 HCC-related deaths) reporting the association between premorbid body mass index (BMI), and HCC-related mortality. We estimated summary adjusted hazard ratio (aHR) with 95% confidence intervals (CIs), comparing obese (BMI>30 kg/m 2 ) and overweight (BMI, 25 to 29.9 kg/m 2 ) individuals with normal BMI individuals using random-effects model. Results: On meta-analysis, compared with individuals with normal BMI, obese (aHR, 1.95; 95% CI, 1.46-2.46), but not overweight individuals (aHR, 1.08; 95% CI, 0.97-1.21), had higher HCC-related mortality, with moderate heterogeneity. On subgroup analysis, magnitude of increased mortality was higher in obese men (aHR, 2.50; 95% CI, 2.02-3.09; 3 studies) as compared with obese women (aHR, 1.45; 95% CI, 1.08-1.97; 2 studies). The impact of premorbid obesity on HCC-related mortality was observed only in western populations (aHR, 2.10; 95% CI, 1.77-2.48; 4 studies), but not Asian populations (aHR, 1.10; 95% CI, 0.63-1.92; 1 study). There was limited assessment of competing risk because of advanced liver disease. Conclusions: On the basis of this meta-analysis, premorbid obesity may be independently associated with a 2-fold risk of HCC-related mortality. This association was more pronounced in men and western populations. Strategies targeting obesity-associated metabolic abnormalities may provide novel pathways for HCC therapy. Abstract : Supplemental Digital Content is available in the text.